Bogota urban art o graffiti. Between illegality and artistic form of expression - Gama-Castro, M. Martha; León-Reyes, Freddy (Arte, Individuo y Sociedad, 2016)
The research related to urban graffiti art, design and visual communication, social culture and politics in the city of Bogota, are issues that this research focus. Reviews and interviews were revealing the influence on the community, civil society, politics and the radical confrontation with the law, their classification and their demand different social strata have made public spaces in Bogota a city with walls speakers. Although it is not taken as a bad thing, -for some- vandalism to others, awakens in many different opinions and above all understated assessment of the artists towards a liberal and democratic expression of a system that moves away from any display of traditional art. bición del arte tradicional.
Keywords: graffitti; expression; society; illegality; street art